Investigation of structural, textural, optical and photocatalytic properties of Sn/TiO₂ nanocomposites - Khalyavka, T.A.; Camyshan, S.V.; Davydenko, L.A.; Permyakov, V.V.; Shcherbakov, S.N. (Functional Materials, 2018)
Nanoscale composite materials based on titanium dioxide and tin were obtained. The obtained powders were characterized by XRD, EDS, SEM, TEM, BET and UV-VIS spectroscopy. The XRD spectrum reveals anatase and rutile structure. Increasing the amount of tin in the composites leads to increase of crystallite size, lattice parameters, pore radius and decrease of specific surface area and pore volume. Analysis of nitrogen sorption-desorption isotherms for the synthesized samples showed the presence of a hysteresis loop which is the evidence for mesoporous structure of the powders. Absorption spectra of the nanocomposites showed a bathochromic shift as compared with pure TiO₂. It was found that tin additives leads to band gap narrowing of TiO₂. Photocatalytic activity of some cationic dyes (Safranin T, Rhodamine C) under UV and visible irradiation in the presence of composites of Sn/TiO₂ was investigated. The composite samples were photocatalytically active in destruction of the cationic dyes in water solutions under UV and visible irradiation. It may be connected with the narrowing of band-gap width, participation of tin in inhibition of electron-hole recombination, prolongation of charges lifetime, increasing of efficiency of interfacial charge separation from TiO₂ to tin and formation of doping electronic states.